Defined spaces - Guimaray Huerta, Héctor Carlos (2012)
Mathematics has been developed, using axioms, mathematical spaces as vector spaces, normed, metric, topological and so on. The primary objective in this article is to define a space in which the properties of a set are the same in the spaces above, for which is considered a function set to set called defined function.